Table of Content - - (Journal of agricultural, environmental and veterinary sciences, 2023)
Table of Content: 1. Taxonomic study of Wild Species of the Brassicaceae Family in Diyala Province-Iraq Asst-Prof. Nisreen Sabbar Hashim , Prof. Wisam Malik Dawood , Prof. Ayyad Wajih Al-Shahwany 2. Taxonomy of starred Agama Laudakia stellio in Syria using morphological Data and 12s rDNA in mitochondrial DNA Dr. Aroub M. Al-Masri, Banan Al-Shaikh, Ismaeel Al-Saleh, Dr. Manar Makhoul 3. Contract farming in Gallo municipality (A development vision for semi-urban farms) Co-Prof. JADALLA. A.E. OMAR , Co-Prof. Ibrahim Ali Elduhere 4. Effect of Briming treatment and boron element on germination properties of some Solanaceae species Mr. Mouhamed Ali Mahmoud Al-Hamoud Al-Arab, Dr. Hussein Qadban Al-Mohamed 5. The Role of Rural Women in Developing Animal and Poultry Production in Some Villages of Menoufia Governorate, Egypt Salem Abdel Hamid Salem , Mervat Shehata Armanous, Shimaa Abdel Mageed El- Kholy 6. Implementation of extension workers for the tasks of agricultural extension programs in some governorates of Lower Egypt Mr. Abdelghany Mohamed Abdeldayem Naser , Mr. Mohamed Abdel-Ghaffar El-Badrawy Hussein , Mrs. Eman Mohammed Mohammed Ebrahim Salem 7. Extension specialists’ vision of marketing problems for agricultural crops and how to confront them in light of the state’s approach to achieving food security in some governorates - Arab Republic of Egypt Prof. Mohamed Youssef Shalaby, Dr. Ahmed Anter Bekheit, Dr. Islam Hassan Sakr , Dr. Hanan Fathi Mekawy , Dr. Tayseer Mumtaz El-Assar 8. Effect of organic and Biofertilizers application on yield of Nigella Sativa L. plant Mrs. Anwar Hussein Nassif, Dr. Najm Abdullah Jumaa Al-Zubaidy, Dr. Rabab Majead Abd 9. Feeding common carp fish on diets containing different percentages of ginger (Zingbar officinale) and its effect on the characteristics of the blood and biochemical parameters Mr. Omar AbdulHameed Al-Kurjia